2019
DOI: 10.2135/cropsci2018.11.0688
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Founding Accessions and Patterns of Relatedness and Inbreeding Derived from Historical Pedigree Data in a White Clover Germplasm Collection in New Zealand

Abstract: Pedigrees provide suitable input for tracking breeding crosses and monitor plants and animal populations. Pedigree analysis is an essential tool to visualize and describe population structure and genetic diversity. Pasture plant breeding relies on a range of strategies from closed system recurrent selection using elite cultivars to diversity‐focused programs using ecotypes and wild germplasm as parents. There is currently no published pedigree analysis of white clover (Trifolium repens L.), despite over a cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…The results from the Trifolium species in this study are comparable to the results by [29,30], where diversity within the white and red clover accessions at the MFGC were assessed. Overall, the level of variation was high across all of the Trifolium species accessions.…”
Section: Genetic Resources For Trifolium Improvementsupporting
confidence: 78%
See 4 more Smart Citations
“…The results from the Trifolium species in this study are comparable to the results by [29,30], where diversity within the white and red clover accessions at the MFGC were assessed. Overall, the level of variation was high across all of the Trifolium species accessions.…”
Section: Genetic Resources For Trifolium Improvementsupporting
confidence: 78%
“…The high levels of diversity found in the genebank collections reported in white [29] and red clover [30] are positive for future hybridisation programmes. Prebreeding efforts in minor Trifolium species could complement white and red clover breeding [29]. showed that the country of origin of accessions has influence on the population structure.…”
Section: Genetic Resources For Trifolium Improvementmentioning
confidence: 93%
See 3 more Smart Citations